Safety and Practice for Organic Food - Biswas, Debabrata; Micallef, Shirley A. (Academic Press, 2019)
Safety and Practice for Organic Food covers current food safety issues and trends. It provides detailed information on all organic and pasture practices including produce-only, farm-animal-only or integrated crop-livestock farming, as well as the impact of these practices on food safety and foodborne infections. The book explores food products that organic, integrated and traditional farming systems are contributing to consumers. As the demand for organic food products grows faster than ever, this book discusses current and improved practices for safer products. Moreover, the book explores progressive directions, such as the application of next-generation sequencing and genomics to aid in the understanding of the microbial ecology of the agro-environment and how farmer education can contribute to sustainable and safe food. Safety and Practice for Organic Food is a unique source of organic agricultural practices and food production for researchers, academics and professionals at agriculture-based universities and colleges who are involved in food science, animal sciences including poultry science, food safety, food microbiology, plant science and agricultural extension. This book is also an excellent source of information for regulators and federal government officials (USDA, FDA, EPA) and the food processing industry.
Keywords: Natural foods -- Safety measures -- Handbooks, manuals, etc.; Natural foods industry -- Quality control -- Handbooks, manuals, etc.; elektronické knihy; electronic books